Two Novel and Three Recurrent Mutations in the Mevalonate Pathway Genes in Chinese Patients with Porokeratosis - Wang X; Ouyang X; Zhang D; Zhu Y; Wu L; Xiao Z; Yu S; Li W; Li C (Dove Medical Press, 2024)
Xiuping Wang,1 Xiaoliang Ouyang,2 Deng Zhang,1 Yunxia Zhu,1 Liang Wu,1 Zhen Xiao,3 Simin Yu,1 Wei Li,2 Chunming Li1 1Department of Dermatology, The Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People's Republic of China; 2Department of Plastic Surgery, The Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People's Republic of China; 3Department of Dermatology, Taiyuan Central Hospital, Taiyuan, Shanxi, People's Republic of ChinaCorrespondence: Chunming Li, Department of Dermatology, The Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People's Republic of China, Tel/Fax +86 791 86278821, Email chunminglincu@163.comPurpose: Porokeratosis (PK) is a chronic autosomal-dominant cutaneous keratinization disorder exhibiting clinical and genetic heterogeneity. Mevalonate decarboxylase (MVD), farnesyl diphosphate synthase (FDPS), phosphomevalonate kinase(PMVK), and mevalonate kinase genes(MVK), which encode the mevalonate pathway, are disease-causing genes in PK.Patients and Methods: Data and blood samples were collected from two Chinese families and five sporadic patients with porokeratosis. Whole-exome and Sanger sequencing were performed to detect pathogenic gene mutation in the patients.Results: Five heterozygous mutations were identified, including a novel FDPS stop-gain mutation c.438T>G (p.Tyr146Ter), a novel MVD missense mutation c.683G>C (p.R228P), and three previously reported MVD mutations: c.746T>C (p.F249S), c.875A>G (p.N292S), and c.1111_1113del (p.371_371del). The novel FDPS c.438T>G mutation was predicted as "disease-causing" (p = 1) by Mutation Taster. The other novel MVD c.683G>C was also predicted as "deleterious" (score = 0.00) by Sorting Intolerant From Tolerant (SIFT), "probably damaging" (score = 1) by PolyPhen2, and "disease-causing" (p = 0.999) by Mutation Taster.Conclusion: Our results extended the mutation spectrum of mevalonate pathway genes in porokeratosis and provided useful strategies for a more accurate diagnosis and genetic counseling.Keywords: porokeratosis, mutation, MVD, FDPS, genetics